Development and verification of a new nuclear data processing system FRENDY - Tada, Kenichi; Nagaya, Yasunobu; Kunieda, Satoshi; Suyama, Kenya; Fukahori, Tokio (Journal of nuclear science and technology, 2017)
Japan Atomic Energy Agency developed the new nuclear data processing system FRom Evaluated Nuclear Data librarY to any application (FRENDY) in order to solve the problems of the current widely used nuclear data processing systems and process the new evaluated nuclear data file. Verification of FRENDY was carried out by three steps, i.e. verification of each function, comparison of the results, and comparison of the k eff values for the 79 benchmark experiments in the ICSBEP handbook using cross section data library processed by FRENDY with those by NJOY99. These results verified that FRENDY generates the ACE (A Compact ENDF) file correctly.